Local professionals' perceptions of health assets in a low-SES Dutch neighbourhood: a qualitative study - Lea Den Broeder; Ellen Uiters; Aafke Hofland; Annemarie Wagemakers; Albertine Jantine Schuit (BMC, 2017)
Abstract Background Asset-based approaches have become popular in public health. As yet it is not known to what extent health and welfare professionals are able to identify and mobilise individual and community health assets. Therefore, the aim of this study was to understand professional's perceptions of health and health assets. Methods In a low-SES neighbourhood, 21 health and welfare professionals were interviewed about their definition of health and their perceptions of the residents' health status, assets available in the neighbourhood's environment, and the way residents use these assets. A Nominal Group Technique (NGT) session was conducted for member check. Verbatim transcripts of the semi-structured interviews were coded and analysed using Atlas.ti. Results The professionals used a broad health concept, emphasizing the social dimension of health as most important. They discussed the poor health of residents, mentioning multiple health problems and unmet health needs. They provided many examples of behaviour that they considered unhealthy, in particular unhealthy diet and lack of exercise. Professionals considered the green physical environment, as well as health and social services, including their own services, as important health enhancing factors, whereas social and economic factors were considered as major barriers for good health. Poor housing and litter in public space were considered as barriers as well. According to the professionals, residents underutilized neighbourhood health assets. They emphasised the impact of poverty on the residents and their health. Moreover, they felt that residents were lacking individual capabilities to lead a healthy life. Although committed to the wellbeing of the residents, some professionals seemed almost discouraged by the (perceived) situation. They looked for practical solutions by developing group-based approaches and supporting residents' self-organisation. Conclusions Our study shows, firstly, that professionals in the priority district Slotermeer rated the health of the residents as poor and their health behaviour as inadequate. They considered poverty and lack of education as important causes of this situation. Secondly, the professionals tended to talk about barriers in the neighbourhood rather than about neighbourhood health assets. As such, it seems challenging to implement asset-based approaches. However, the professionals, based on their own experiences, did perceive the development of collective approaches as a promising direction for future community health development.